The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1101/653311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cochlear activity in silent cue-target intervals shows a theta-rhythmic pattern and is correlated to attentional alpha modulations

Abstract: There is still a controversial debate regarding, where in the processing hierarchy of the central nervous system (CNS) selective attention takes effect. The auditory system can influence cochlear processes via direct and mediated (by the inferior colliculus) projections from the auditory cortex to the superior olivary complex (SOC). Studies illustrating attentional modulations of cochlear responses have so far been limited to sound evoked responses. The aim of the present study was to investigate intermodal (a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Furthermore, this subcortical activity can even be modulated by attention ( 19, 20, 23 ). Interestingly, top-down attentional modulations of auditory activity can already be detected at the hair cells in the inner ear measured as otoacoustic activity (faint sounds emitted by the outer hair cells; see 24 ). Other studies have shown that even subcortical nuclei on the auditory pathway are behaviorally relevant for speech recognition (medial geniculate bodies; 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this subcortical activity can even be modulated by attention ( 19, 20, 23 ). Interestingly, top-down attentional modulations of auditory activity can already be detected at the hair cells in the inner ear measured as otoacoustic activity (faint sounds emitted by the outer hair cells; see 24 ). Other studies have shown that even subcortical nuclei on the auditory pathway are behaviorally relevant for speech recognition (medial geniculate bodies; 25 ).…”
Section: Resultsmentioning
confidence: 99%